A longitudinal assessment of the bivalent fear of evaluation model with social interaction anxiety in social anxiety disorder. Issue 12 (1st October 2020) - Johnson, Andrew R.; Bank, Samantha R.; Summers, Mark; Hyett, Matthew P.; Erceg‐Hurn, David M.; Kyron, Michael J.; McEvoy, Peter M.
Abstract: Background: The Bivalent Fear of Evaluation Model proposes that the fears of positive and negative evaluation each uniquely contribute to social anxiety severity. However, the debate continues as to whether these are distinct constructs, and, if so, the degree of influence each has on social anxiety severity. This study used a longitudinal evaluation of these relationships in a clinical sample to identify whether the two fears differentially change over time and differentially relate to social anxiety severity. Methods: Individuals with a social anxiety disorder ( N = 105) completed measures of fears of negative and positive evaluation weekly, and social interaction anxiety monthly, for 12 weeks. Temporal relationships were assessed using residual dynamic structural equation modeling. Results: Fears of positive and negative evaluation both predicted the future status of the other ( ϕ = 0.18, 95% credibility interval [0.10–0.28] and ϕ = 0.22 [0.12–0.35], respectively). Fear of negative evaluation ( ϕ = 0.16 [0.05–0.28]) but not positive evaluation ( ϕ < 0.01 [−0.09 to 0.10]) directly predicted future social anxiety severity. Fear of positive evaluation only indirectly predicted anxiety severity via fear of negative evaluation. Conclusions: Previous fears of negative evaluation could not fully explain future fears of positive evaluation (or vice‐versa), which is consistent with the two constructs being likely distinct in social anxiety disorder. Given its more direct relationship with social anxiety severity, fear of negative evaluation should be targeted in treatment, as this could both directly reduce social anxiety severity and minimize the indirect impact of fear of positive evaluation.